Enhancing Students’ Reading Comprehension Through Jigsaw - Putriani, Ni Putu Ika; Krismayani, Ni Wayan Krismayani; Arsana, Anak Agung Putu (International Journal of Applied Science and Sustainable Development (IJASSD), 2024)
One of the linguistic skills that students should focus on learning is reading comprehension. Most junior high school students struggled with their reading abilities. This study aimed to investigate if Jigsaw combined with pictures may enhance the reading comprehension of seventh-grade students at SMPN 12 Denpasar in the academic year 2022/2023 through action research conducted in the classroom. Pre-test, post-test, and questionnaire activities were, therefore, part of the researchers’ efforts to meet the goal of the current study. The pre-test results from the pre-cycle indicated that the subjects' reading comprehension skills, mainly when it came to reading descriptive texts, were categorized as good. The current action research in the classroom was then conducted using a Jigsaw combined with pictures. The result of the post-test I in the second session showed that the subjects' progress decreased compared to the previous pre-test. In addition, the result of the post-test II in the last session showed significant progress concerning the subjects' ability in reading comprehension, which improved from sound level to excellent. Additionally, this study demonstrated that the individuals' favorable reactions to the method used to increase their reading comprehension changed their learning behavior. In conclusion, the current classroom action research showed that using Jigsaw combined with pictures could enhance the reading comprehension of seventh-grade students at SMPN 12 Denpasar in the academic year 2022/2023. The subjects also gave positive responses.